Making Spoken Word on Combat - Hast, Susanna (Rowman & Littlefield, 2023)
This chapter discusses a spoken word piece written and recorded in a research project investigating somatic social bonding among the Finnish Defence University cadets. It illustrates how sensual and sensory experience can be modes of insight through which difficult questions around soldiering can be examined. In the spoken word piece Hast & Cast: Ei niin pelottava asia (2019), the text is constructed from interview data while voice, rhythm, amplification, and repetition all work to open up a space of wonder and association. This humorous and disturbing research-creation is not only meant for academic audiences, but it speaks back to the cadets in a language that is accessible and thought-provoking. This chapter demonstrates how the artistic manipulation of research data addresses the paradoxical emotional stakes of military training by tapping into the rhythmic, corporeal, and sonic qualities on which military training also relies.
Keywords: sotilaat; taiteellinen tutkimus; musiikki; kadetit; sotilaskoulutus; ruumis; tunteet